Mutation screening of α-crystallin mutations in congenital cataract patients - Manoj Kumar; Rima Dada; Tushar Agarwal; Sudarshan Khokhar (Delhi Journal of Ophthalmology)
Purpose: To screen α-crystallin (CRYAA) gene in congenital cataract patients and controls. Methods: Fifty clinically diagnosed congenital cataract cases below 3 years of age from northern India, presenting at Dr. R. P. Centre for Ophthalmic Sciences (AIIMS, New Delhi, India) were enrolled in this study. Genomic DNA was extracted from peripheral blood, all coding and exon/intron regions were amplified using PCR and direct sequencing was performed to detect any nucleotide variation. Results: The mean age of the patients was 1.75±0.19 years. The age of onset was recorded as the age at which the disease was first noticed by the child’s parents or first documented by a cli-nician. All cases were sporadic and 32 were males and 18 were females. None of the cases were product of consanguineous marriage and all patients had bilateral lens opacification. The degree of opacification showed variability among patients as 58% (29/50) of patients had nuclear cataract, 28% (14/50) with lamellar/zonular cataract and 8% (4/50) had anterior polar cataract and 6% (2/50) had total cataract. Conclusion: This study shows that the pathogenesis of the majority of congenital cataract cas-es in North India seems not to be accounted for mutations by the coding exons of α-crystallins. It is also possible that currently unidentified genes may be a more significant cause of cataract than previously thought. Based on this study CRYAA has no role in congenital cataract in north Indian population.